2022
DOI: 10.5423/ppj.oa.01.2022.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arugula Vermicompost on the Root-Knot Nematode (Meloidogyne javanica) and the Promotion of Resistance Genes in Tomato Plants

Abstract: Root-knot nematodes are the most important plantparasitic nematodes worldwide. Many efforts have been made to find non-chemical, risk-free, and environmentally friendly methods for nematode control. In this study, the effects of compost and vermicompost of arugula (Eruca sativa) on Meloidogyne javanica were investigated in three glasshouse experiments. In addition, the expression of the defense-related genes nonexpressor of pathogenesis-related 1 (NPR1) and lipoxygenase 1 (LOX1) was detected in tomato plants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The results of the present study in the first glasshouse experiment showed that all organic materials used in this study increased the dry weight of shoots of infected and healthy tomato plants, except for the sulfur treatment. Similar to our previous studies, the plant dry weight index compared to the fresh weight index better defined the difference between treatments and their effects [ 30 , 39 ]. Only the arugula vermicompost caused a significant reduction in the reproduction factor of the root-knot nematode Meloidogyne javanica .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The results of the present study in the first glasshouse experiment showed that all organic materials used in this study increased the dry weight of shoots of infected and healthy tomato plants, except for the sulfur treatment. Similar to our previous studies, the plant dry weight index compared to the fresh weight index better defined the difference between treatments and their effects [ 30 , 39 ]. Only the arugula vermicompost caused a significant reduction in the reproduction factor of the root-knot nematode Meloidogyne javanica .…”
Section: Discussionsupporting
confidence: 69%
“…Earthworms improve the properties of organic material to produce compost, and vermicompost is superior to compost in producing plant biomass [ 57 ]. Thus, vermicomposting of arugula increases the content of N, P, Fe and Mg, and lowers pH [ 39 ]. Due to the nematicidal nature of arugula plants, vermicompost production increased the utility and quality of vermicompost and arugula plants as soil amendments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arugula Vc also decreases the reproduction factor of the nematode by 54.4 to 70.5% in infected tomato plants. It affects the expression of resistance genes and induces systemic resistance against root-knot nematodes ( Rostami et al, 2022 ). Moreover, soil application of AMF fungi also reduced plants’ root galling and nematode population ( Siddiqui and Akhtar, 2007 ).…”
Section: Discussionmentioning
confidence: 99%